The global regime for the enforcement of intellectual property rights - Seuba, Xavier, 1977- (Cambridge University Press, 2017)
"The Global Regime on Border Measures", deals with the international regulation of border controls of goods protected by intellectual property rights. Since the TRIPS Agreement introduced the first comprehensive multilateral regulation on border measures relating goods protected by intellectual property rights, numerous plurilateral and bilateral treaties have expanded border measures. Chapter 10 underlines that border measures are the enforcement-related remedy most frequently regulated in post-TRIPS treaties. Originally focused on the control on importation of counterfeit and pirated goods, international obligations related to border controls have expanded to cover all customs situations and intellectual property categories. New regulations have expanded right holders' rights in the context of border enforcement, while paying little attention to the rights of other concerned parties"--Provided by publisher